THE INFLUENCE OF JOB CRAFTING ON WORK ENGAGEMENT THROUGH WORK MEANING IN PT EMPLOYEES. SPIL (SALAM PACIFIC INDONESIA LINES) - Dandy Ahsani Taqwim; Fendy Suhariadi (Media Bina Ilmiah, 2024)
Logistics service companies in Indonesia play an important role in facilitating the distribution of goods and services, such as PT. Spill. The existence of Job Crafting problems due to less harmonious employee relations causes low employee Work Engagement as evidenced by data changes. Apart from that, it is also influenced by employment factors. Meaning of employee work. The research aims to analyze the influence of Job Crafting on Work Meaning and Work Engagement at PT SPIL, as well as the influence of Work Meaning on Work Engagement; and the influence of Job Crafting on Work Engagement is mediated by the Meaning of Work at PT SPIL. The research uses quantitative methods. The sample population was 320 respondents. Data collection techniques through questionnaires with PLS to analyze data. The research results concluded that Job Crafting had a significant effect on Work Meaning and Work Engagement of PT SPIL Employees; The meaning of work has a significant effect on the work engagement of PT SPIL employees; and Work Meaning is able to mediate the relationship between Job and Work Engagement of PT SPIL Employees